1981
DOI: 10.1073/pnas.78.6.3920
|View full text |Cite
|
Sign up to set email alerts
|

Impaired induction and self-catabolite repression of extracellular pectate lyase in Erwinia chrysanthemi mutants deficient in oligogalacturonide lyase

Abstract: The pectate lyase (PL; EC 4.2.2.2) secreted by the plant pathogen Erwinia chrysanthemi is induced and catabolite repressed by different concentrations of its own product, digalacturonic acid 4,5-unsaturated at the nonreducing end [u(GalUA) 2 ]. Both activities of u(GalUA) 2 depend on its cleavage by oligogalacturonide lyase (OGL; EC 4.2.2.6). This intracellular enzyme converts u(GalUA) 2 to the deoxyketuronic acid 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…Pectate lyase induction appears to be an autocatalytic process in which extracellular degradation of the substrate by basal levels of secreted pectic enzymes results in the release of assimilable oligogalacturonates, which signal the presence of the polymer (6,7). The induction of pectate lyase by the Peh-mutant CUCPB5008 was significantly reduced relative to the wild type.…”
Section: Discussionmentioning
confidence: 85%
“…Pectate lyase induction appears to be an autocatalytic process in which extracellular degradation of the substrate by basal levels of secreted pectic enzymes results in the release of assimilable oligogalacturonates, which signal the presence of the polymer (6,7). The induction of pectate lyase by the Peh-mutant CUCPB5008 was significantly reduced relative to the wild type.…”
Section: Discussionmentioning
confidence: 85%
“…These mutants are also unable to grow on pectin or PGA as the sole carbon sources (402). Expression of pectinase genes (pemA, pelB, pelC, pelD, and pelE) and of genes of the intracellular part of the pectin degradation pathway (ogl, kdul, and kdgT) is dramatically reduced in crp mutants (84). Similarly, an E. carotovora cya mutant (defective in cAMP production) is defective in Pel synthesis (336).…”
Section: Vol 69 2005mentioning
confidence: 99%
“…Early physiological studies suggested that pectinase production in Erwinia species is subject to catabolite repression (221). Catabolite repression was observed during growth in the presence of glucose and also in the presence of pectin catabolic products (84,491). The cyclic AMP (cAMP) receptor protein (CRP) is essential for this regulation ( Fig.…”
Section: Vol 69 2005mentioning
confidence: 99%
See 1 more Smart Citation
“…Pectin degradation by the phytopathogenic enterobacterium Erwinia chrysanthemi has been extensively studied (20 5-Keto-4-deoxyuronate (DKI) is the primary product formed by the catabolism of polygalacturonate by the pectate lyases and oligogalacturonate lyase (6,17,18) (Fig. 1).…”
mentioning
confidence: 99%